An investigation into the job Design of construction managers and its impact on employee engagement - Bosa, Nikita; Mtetwa, Trevor Ncamiso (Technium Social Sciences Journal, 2023)
The aim on construction contractors is to increase their output, decrease employee turnover, enhance stakeholder management and ensure that maintain competitiveness. Employee commitment and engagement is a tool that can drive enhance the achievement of these objectives. Disengaged employees have been linked to higher absenteeism and turnover, lower attention to detail and lack of team integration, aspects that all impact negatively on project performance/productivity. This paper assessed employee engagement and perception of job design of construction managers within a major construction contractor. A quantitative approach by means of electronic email survey was used for collecting primary data. A census survey was conducted, and data was collected from the full population of 11 construction managers. Data was analysed using SPSS. The data was presented in a combination of frequency and descriptive statistics. Overall employee engagement levels were found to be high amongst respondents. The lowest composite measure was for employee loyalty and the highest was for employee commitment. Perceptions of job design attributes were also high indicating that the work of construction managers is well designed. Information and processing achieved the highest rating while task significance scored the lowest. Recommendations to assist in increasing existing levels of employee engagement and job design included, greater commitment from organisational leadership to drive the agenda, training and career development and planning.